Corticosteroids and tocilizumab reduce in-hospital mortality in severe COVID-19 pneumonia: a retrospective study in a Spanish hospital. Issue 4 (3rd April 2021) - Van den Eynde, E.; Gasch, O.; Oliva, J. C.; Prieto, E.; Calzado, S.; Gomila, A.; Machado, M. L.; Falgueras, L.; Ortonobes, S.; Morón, A.; Capilla, S.; Navarro, G.; et al.
Abstract: Background: There is an urgent need to reduce mortality of COVID-19. We examined if corticosteroids and tocilizumab reduce risk for death in patients with severe pneumonia caused by SARS-CoV-2. Methods: A retrospective cohort study was performed in a single university hospital. All adult patients admitted with confirmed severe COVID-19 pneumonia from 9 March to 9 April 2020 were included. Severe pneumonia was defined as multi-lobar or bilateral pneumonia and a ratio of oxygen saturation by pulse oximetry to the fraction of inspired oxygen (SpFi)<315. All patients received antiviral and antibiotic treatment. From March 26, patients also received immunomodulatory treatment with corticosteroids (methylprednisolone 250 mg/day for 3 days), or tocilizumab or both. In-hospital mortality in the entire cohort and in a 1:1 matched cohort sub-analysis was evaluated. Results: 255 patients were included, 118 received only antiviral and antibiotic treatment while 137, admitted after March 26, also received immunomodulators. In-hospital mortality of patients on immunomodulatory treatment was significantly lower than in those without [47/137(34.3%) vs. 69/118(58.5%), ( p < .001)]. The risk of death was 0.44 (CI, 0.26–0.76) in patients receiving corticosteroids alone and 0.292 (CI, 0.18–0.47) in those treated with corticosteroids and tocilizumab. In the sub-analysis with 202 matched patients, the risk of death was 0.356 (CI 0.179–0.707) in patients receiving corticosteroids alone and 0.233 (0.124–0.436) in those treated with the combination. Conclusions: Combined treatment with corticosteroids and tocilizumab reduced mortality with about 25% in patients with severe COVID-19 pneumonia. Corticosteroids alone also resulted in lower in-hospital mortality rate compared to patients receiving only antiviral and antibiotic treatment. Corticosteroids alone or combined with tocilizumab may be considered in patients with severe COVID-19 pneumonia.